2015
DOI: 10.7287/peerj.preprints.881v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Childhood socioeconomic deprivation, but not current mood, is associated with behavioural disinhibition in adults

Abstract: There is evidence to suggest that impulsivity is predicted by socioeconomic background, with people from more deprived backgrounds tending to be more impulsive, and by current mood, with poorer mood associated with greater impulsivity. However, impulsivity is not a unitary construct, and previous research in this area has focused on measures of ‘waiting’ impulsivity rather than behavioural disinhibition. We administered a standard measure of behavioural disinhibition, the stop-signal task, to 58 adult particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…For example, early life experiences of scarcity have long‐lasting effects on people's executive functioning. Meta‐analyses show a medium‐size correlation between childhood socioeconomic status (SES) and executive functioning in children (Lawson, Hook, and Farah ) as well as executive functioning in adult life (Mittal et al , 10; Paál, Carpenter, and Nettle ). In the face of current economic uncertainty, adults “who grew up in lower‐SES environments were more impulsive, took more risks, and approached temptations more quickly” (Griskevicius et al , 197).…”
Section: The Human Capital Catch‐22: Life Factors That Create Need Fomentioning
confidence: 99%
“…For example, early life experiences of scarcity have long‐lasting effects on people's executive functioning. Meta‐analyses show a medium‐size correlation between childhood socioeconomic status (SES) and executive functioning in children (Lawson, Hook, and Farah ) as well as executive functioning in adult life (Mittal et al , 10; Paál, Carpenter, and Nettle ). In the face of current economic uncertainty, adults “who grew up in lower‐SES environments were more impulsive, took more risks, and approached temptations more quickly” (Griskevicius et al , 197).…”
Section: The Human Capital Catch‐22: Life Factors That Create Need Fomentioning
confidence: 99%
“…$5 now versus $10 next month) and earlier reproduction [33]. In a UK community sample, adults who had lived in more deprived neighborhoods at age 16 show greater behavioral disinhibition [34]. In Brazil, favela youth discount the future more than university students from more affluent neighborhoods [35] and less well off students choose careers that offer quicker returns and require smaller investments than wealthier students [36].…”
Section: Empirical Researchmentioning
confidence: 99%
“…236-237). These patterns focus on short-term interests, increasing impulsive, sensory and hedonistic behaviour (see Frankenhuis, Panchanathan and Nettle, 2016, p. 76;Páal, Carpenter and Nettle, 2015). Adams et al, for example, found that 'Greater anticipated survival was cross-sectionally associated with lower likelihood of smoking, and higher physical activity levels', while 'Lower anticipated survival was associated with decreased probability of adopting healthier patterns of physical activity, and increased probability of becoming a smoker at follow up' (2015, p. 1).…”
Section: Domination and Work-related Stressmentioning
confidence: 99%